Information Skills of Finnish Basic and Secondary Education Students: The Role of Age, Gender, Education Level, Self-efficacy and Technology Usage - Meri-Tuulia Kaarakainen; Loretta Saikkonen; Juho Savela (Universitetsforlaget, 2018)
Abstract The information skills and technology use of 3,159 Finnish 12-22-year-old students were examined in this study. Data were collected using the combination of a usage habit questionnaire and a performance-based test that measured their skills when choosing a medium to seek information, defining search queries, and selecting and evaluating search results. On average, these students' information skills were found to be insufficient. Particularly, students failed in creating search phrases, and they tended to concentrate on content relevance at the expense of source reliability. Versatility of technology use was found to be the most prominent predictor of students' information skills. Education level also had an increasing effect on information skills, whereas age alone, within separate education levels, did not have the same effect. Self-efficacy was found to be associated only with male students' information skills. Gender had no direct effect on information skills; rather it was identified as a moderator for the ongoing relationship between information skills and technology use.